After the beginning : a cosmic journey through space and time - Glendenning, Norman K. (World Scientific ; Imperial College Press, 2004)
In a brilliant flash about fourteen billion years ago, time and matter were born in a single instant of creation. An immensely hot and dense universe began its rapid expansion everywhere, creating space where there was no space and time where there was no time.